Sketches of Iceland in Xavier Marmier’s Lettres d’Islande (1837) and Henry Labonne’s L'Islande et l'archipel des Færoeer (1888): saga-steads challenging the poetics of ruins - Mossé, Marie (HAL CCSD, 2016)
International audience